Evaluation of Storage and Disposal of Household Waste in the City of Kinshasa - Frey, Sylvestre; Kibamba, Nestor Anzola; Makanua, Diansambu (Research Advances in Environment, Geography and Earth Science Vol. 6, 2024)
This study aims to analyze and describe the characteristics of household waste in the communes of Lemba, Mont-Ngafula and Kisenso in Kinshasa, as well as their storage and disposal methods while raising awareness of ecological citizenship. Solid waste disposal in households is an urgent issue that needs to be addressed. In cities without urban planning and health and environmental regulations, residents face inadequate living conditions. The study was conducted from April 17 to May 3 2023, with a sample of 690 households, with 138 households randomly selected from each municipality. The main methods used are survey, maintenance and field observation. The findings demonstrate that managing household garbage does not promote sustainable development in the cities under investigation. With the exception of the Kindule region, most homes use buckets and bags for their garbage cans; waste sorting is uncommon. The two most popular methods of disposing of waste are incineration and inappropriate local disposal. The two most popular ways to dispose of waste are combustion and improper disposal. The average weight of waste varies by district, with values ranging from 8.67 kg to 13.99 kg per household. There is a significant correlation between the total weight of waste generated per household and the size of the household. The results of the study indicate that the state of household waste management in these cities is worrying, with harmful consequences for the environment and public health. The building of landfills, new waste management regulations, the incorporation of waste management into urban development plans, and raising public knowledge of sanitation laws and the principles of waste reduction, reuse, and recycling are all included in the suggestions. It is crucial to develop effective and sustainable strategies to address household waste management in these communities in Kinshasa. The involvement of local authorities, stakeholders and citizens is essential to protect the environment. There is a need to find effective and sustainable solutions to solve the problems of household waste management in the communes of Lemba, Kisenso and Mont-Ngafula in Kinshasa.